Pengembangan Keterampilan Sosial Siswa Sekolah Dasar dalam Konteks Pendidikan Multikultural Pada Mata Pelajaran IPS: Indonesia - Eka Saputra, Erwin (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
Multicultural education in elementary schools plays an important role in shaping students' social skills. This education teaches students to appreciate cultural,. ethnic, religious, and linguistic diversity in everyday life. This article aims to discuss how elementary school students' social skills are developed through a multicultural education approach. By using various teaching methods and schoolprograms, multicultural education helps students understand the values of tolerance, cooperation, and empathy. This study found that students exposed to multicultural education showed significant improvements in social skills, such as openness to differences and the ability to work in diverse groups